PELATIHAN TEKNIK MUDAH PEMBUATAN GAME PADA MICROSOFT POWERPOINT PADA SMK AL-WASLIYAH HAMPARAN PERAK - Titin Setiawati; Muhammad Sabri; Muhammad Munawar Suaib (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Reativity and skills in the field of technology are a unit that go hand in hand and are indispensable in the world of work. For this reason, it needs to be instilled early on in directing and developing the skills and creativity of a student. Given the large number of companies engaged in graphic design, advertising and multimedia, it affects the development of the times and everyone's knowledge. In the very rapid development of technology like now we are required to be able to become people who have more creativity. This Community Service is carried out at the Al-Wasliyah Hamparan Perak Vocational School, where the author will help younger siblings to be able to make simple games from power point. But it doesn't demand the possibility for them to recreate it into games that are more creative, innovative and useful.